Implementasi Sistem Pendeteksi Kematangan Buah Pisang Menggunakan Metode Transformasi Ruang Warna HSI - Martina Halimah; Shindy Qurani Rahim; Arniati Burara; Yolen Perdana Sari; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Bananas are fruit plants that are rich sources of vitamins, minerals and carbohydrates. Bananas also have extraordinary properties, especially for health, one of which can generate hemoglobin so that it can overcome anemia. Bananas can usually be found in vegetable vendors, traditional markets and supermarkets in Indonesia. In general, farmers still classify bananas manually. In this study, the method used is the HSI color space transformation method. The Color Space Transformation method is one of the methods of image processing that is carried out to obtain various color spaces from an image in a certain coordinate system. The advantage of this method is that it can produce one color combination and can use any information in the image. Based on research conducted from several journals to detect the level of ripeness of bananas using the HSI color space transformation method, it can be concluded that detecting the level of ripeness of bananas is not always done manually, but can also be done computerized using the HSI method. So that it can be used to assist farmers in determining the maturity level of bananas so that the quality of bananas can be guaranteed.